Emergency cricothyrotomy in infants - Evaluation of a novel device in an animal model - Metterlein, Tom; Frommer, M.; Kwok, P.; Lyer, Stefan; Graf, B. M.; Sinner, B. (Pediatric Anesthesia, 2011)
Background: According to different algorithms of airway management, emergency cricothyrotomy is the final step in managing an otherwise not accessible airway. As an alternative to an open surgical procedure, minimally invasive approaches exist. Quicktrach baby™ is a commercially available set for a minimal invasive cricothyrotomy in infants. The set consists of a plastic cannula over a metal needle for direct placement in the trachea. So far, this device has not been evaluated for its intended use. Objectives: We hypothesize that Quicktrach baby™ allows the establishment of an emergency airway. The aim was to prove that the device is easy to handle and the cricothyrotomy fast to perform. Methods: After approval of the local ethics committee, the study was performed on the cadavers of 10 adult rabbits. Cricothyrotomy was performed with Quicktrach baby™. Successful placement, performance time, and complication rate were documented. Possible ventilation with a breathing bag was evaluated. Data are reported as mean and interquartile range. Results: Successful placement of Quicktrach baby™ was possible in all attempts. The placement took 31 [23-43] s. In two cases, a fracture of the cricoid's cartilage was seen. In one animal, damage to the posterior wall mucosa was observed. In all cases, sufficient ventilation was possible. Conclusions: Quicktrach™ baby proved to be a reliable technique. In the animal model, it is easy and fast to perform. Only a few minor complications occurred. Sufficient ventilation was possible in all attempts. © 2011 Blackwell Publishing Ltd.
CRIS-Team Scopus Importer:2022-06-27
Keywords: cricothyrotomy; emergency; pediatric airway management; Quicktrach baby™